2021
DOI: 10.1111/nph.17516
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of SnTox3 from the necrotrophic fungus Parastagonospora nodorum reveals a unique effector fold and provides insight into Snn3 recognition and pro‐domain protease processing of fungal effectors

Abstract: Summary Plant pathogens cause disease through secreted effector proteins, which act to promote infection. Typically, the sequences of effectors provide little functional information and further targeted experimentation is required. Here, we utilized a structure/function approach to study SnTox3, an effector from the necrotrophic fungal pathogen Parastagonospora nodorum, which causes cell death in wheat‐lines carrying the sensitivity gene Snn3. We developed a workflow for the production of SnTox3 in a heterol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 95 publications
(178 reference statements)
1
33
0
Order By: Relevance
“…The different pOPIN-GG acceptors are crosscompatible for co-expression, allowing for ease of co-expression and purification of protein complexes. Finally, the utility of the pOPIN-GG vectors presented here have already been successfully tested by the community for the expression and purification of a fungal effector from Parastagonospora nodorum (Outram et al, 2021), as well as for detailing the structural mechanisms underpinning the evolution of Magnaporthe oryzae effectors for a specific host target (Bentham et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The different pOPIN-GG acceptors are crosscompatible for co-expression, allowing for ease of co-expression and purification of protein complexes. Finally, the utility of the pOPIN-GG vectors presented here have already been successfully tested by the community for the expression and purification of a fungal effector from Parastagonospora nodorum (Outram et al, 2021), as well as for detailing the structural mechanisms underpinning the evolution of Magnaporthe oryzae effectors for a specific host target (Bentham et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this lack of a visible phenotype precludes this coexpression approach from being used to study these interactions (as it can be with many biotrophic effectors). Consequently, as an alternative approach, NEs are often expressed using heterologous systems for characterization and subsequent phenotyping on host plants (Liu et al, 2009(Liu et al, , 2012Outram et al, 2021;Sung et al, 2021;Zhang et al, 2017). Almost exclusively, NEs have been expressed by using microbial expression systems such as Escherichia coli and Pichia pastoris.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the cysteines in many of these effectors form disulfide bonds providing stability for these proteins in the apoplast (Saunders et al, 2012). For instance, the Tox3 and Tox1 effectors from P. nodorum contain six and 16 cysteines respectively, and at least one disulfide bond is required for their necrosis-inducing activity (Liu et al, 2009(Liu et al, , 2012Outram et al, 2021). Similarly, Cladosporium fulvum effector Avr2 has four disulfide bonds that are essential for its function of inhibiting cysteine protease Rcr3 in tomato plants (Rooney et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations